Peran Pemerintah dalam Pemberdayaan Masyarakat Pengrajin Noken di Kelurahan Fandoi - Hermanu Iriawan; Edyanto Edyanto (Sosio e-Kons, 2022)
Community empowerment is very important to be carried out by the government. This study aims to determine the role of the government in empowering noken craftsmen in the Fandoi village. This research is descriptive qualitative. Data collection techniques were carried out through observation, interviews, documentation studies, and literature studies. Analysis of the data used is qualitative data analysis. The results showed that there was no government involvement in socializing or providing assistance to community empowerment in Fandoi Village, so the Fandoi Village community built their own business. The community makes a noken bag business without the slightest help from the government. The business of making noken bags has a positive impact, because initially only relying on the husband's income, now they can help and provide additional income.